PM and PAHs emissions of ship auxiliary engine fuelled with waste cooking oil biodiesel and marine gas oil. Issue 1 (26th October 2018) - Su, Peng‐hao; Geng, Peng; Wei, Lijiang; Hou, Chun‐yan; Yin, Fang; Tomy, Gregg T.; Li, Yi‐fan; Feng, Dao‐lun
Abstract : Clean fuels are recommended for ships at berth to reduce air pollutant emissions. This study aimed to evaluate the feasibility of waste cooking oil (WCO) biodiesel application on board with regard to particle matter (PM) and polycyclic aromatic hydrocarbon (PAH) emissions. An experiment was conducted on a marine auxiliary engine for three different fuels: WCO biodiesel, formulation blends with marine gas oil (MGO) and neat MGO. Results revealed that WCO biodiesel could reduce PM and PAHs emissions. WCO exhaust also exhibited differences in PAH profile and phase distribution as compared to MGO, depending on the operation modes and the proportion of biodiesel in the formulation blends. Consequently, WCO biodiesel could dramatically reduce the total carcinogenic potencies related to PAHs of exhausts. Moreover, PAH source recognition pair ratios of tested fuels were observed to deviate from the widely accepted values. This study highlights that WCO biodiesel is a cleaner fuel for operating ship auxiliary engines with respect to PM and PAHs emissions and has the potential to moderate the severe effects of PM and PAHs on an air of coastal areas.